2002
DOI: 10.1034/j.1600-0684.2002.1o005.x
|View full text |Cite
|
Sign up to set email alerts
|

Viral dynamics of early HIV infection in neonatal macaques after oral exposure to HIV‐2287: an animal model with implications for maternal–neonatal HIV transmission

Abstract: A model of vertical HIV transmission was developed using oral HIV-2(287) exposure of newborn Macaca nemestrina. The minimal Animal Infectious Dose for this oral route was found to be 10-fold higher than that for atraumatic viral transmission across other mucosal membranes (vaginal/rectal) of juvenile macaques. However, once infection was established, viral replication was rapid and plasma viremia could be detected by reverse-transcriptase polymerase chain reaction and viral co-culture within 1 week following e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…It has been well described for the past decade or more that a variety of salivary inhibitors decrease HIV-1 infectivity in the oral cavity (108,109). Nonetheless, ongoing studies have suggested that oral transmission of the virus remains quite common in a number of important settings in vivo (6,7,51). These enigmatic processes require significant evaluations to dissect, in a prioritized manner, the full virus:host cell interactions which occur in vivo and lead to oral HIV-1 transmission and pathogenesis.…”
mentioning
confidence: 99%
“…It has been well described for the past decade or more that a variety of salivary inhibitors decrease HIV-1 infectivity in the oral cavity (108,109). Nonetheless, ongoing studies have suggested that oral transmission of the virus remains quite common in a number of important settings in vivo (6,7,51). These enigmatic processes require significant evaluations to dissect, in a prioritized manner, the full virus:host cell interactions which occur in vivo and lead to oral HIV-1 transmission and pathogenesis.…”
mentioning
confidence: 99%
“…Assuming that the viral set-point is determined early in infection (15,42), a better understanding of the mechanisms of oral HIV-1 transmission and early virus-host interactions at mucosal entry sites is needed. The infant rhesus macaque model of simian immunodeficiency virus (SIV) infection is extremely valuable in addressing this question and testing intervention strategies (9,14,16,24,37,38,43,44). We have recently developed a physiologically more-relevant SIV infection model in infant macaques that consists of repeated oral SIV exposures by feeding multiple times daily for a fixed time period to mimic HIV-1 infection via breast-feeding in humans (36,40,43,45).…”
mentioning
confidence: 99%
“…Despite this, oral transmission can occur. For example, SIV transmission across non-traumatised oral epithelia, resulting in dissemination and systemic infection in primates, has been reported in several studies (Baba et al, 1996;Joag et al, 1997;Herz et al, 2002;Milush et al, 2004). As a result, the epithelium may represent either a physical barrier against direct infection or a potential reservoir to aid infection.…”
Section: Introductionmentioning
confidence: 94%